2018
DOI: 10.1371/journal.pone.0204932
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climate change on spring wheat yields in North America and Eurasia in 1981-2015 and implications for breeding

Abstract: Wheat yield dynamic in Canada, USA, Russia and Kazakhstan from 1981 till 2015 was related to air temperature and precipitation during wheat season to evaluate the effects of climate change. The study used yield data from the provinces, states and regions and average yield from 19 spring wheat breeding/research sites. Both at production and research sites grain yield in Eurasia was two times lower compared to North America. The yearly variations in grain yield in North America and Eurasia did not correlate sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 29 publications
4
17
1
Order By: Relevance
“…Our results confirm previous studies that cropping systems have an overriding impact on weed communities' characteristics and associated crop yields (Pollnac et al, 2009, Menalled et al, 2016, Ball et al, 2019. Also, also similar to previous studies (Lanning et al, 2010, Asseng et al, 2015, Morgounov et al, 2018, winter wheat yield declined in response to warmer and drier conditions, but the response varied across cropping systems. In the conventional no-till system, where there was almost no weed biomass, we observed a consistent decline in winter wheat yields in response to warmer and drier conditions regardless of the almost absent crop-weed competition.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirm previous studies that cropping systems have an overriding impact on weed communities' characteristics and associated crop yields (Pollnac et al, 2009, Menalled et al, 2016, Ball et al, 2019. Also, also similar to previous studies (Lanning et al, 2010, Asseng et al, 2015, Morgounov et al, 2018, winter wheat yield declined in response to warmer and drier conditions, but the response varied across cropping systems. In the conventional no-till system, where there was almost no weed biomass, we observed a consistent decline in winter wheat yields in response to warmer and drier conditions regardless of the almost absent crop-weed competition.…”
Section: Discussionsupporting
confidence: 92%
“…For example in the Northern Great Plains of the United States, the region where this study was conducted and a major cereal-producing system, climate change is predicted to increase temperatures by 2.5 -3.3°C in the next 30 years and decrease precipitation during the summer, resulting in increased summer drought stress (Whitlock et al, 2017). To ensure global food security, it is therefore vital we understand how climate change will impact agricultural production by modifying planting and harvesting dates, crop phenological development, grain volume weight, and overall yield (Lanning et al, 2010, Morgounov et al, 2018. Higher temperatures are expected to reduce agricultural production especially of wheat (Triticum aestivium L.), one of the worlds staple commodities (Wilcox & Makowski, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under rainfed conditions, an 11% yield decline in 1973-2010 was reported in Picardy (France), a vital winter wheat-producing region in Europe, where maximum spring temperatures increased by 2.4 °C and total fall precipitation decreased by 9% over the study 1 3 period (Licker et al 2013). Rainfed spring wheat in Eurasia and North America is harmed by high temperature in June and July, when heading, flowering, and ripening occur (Morgounov et al 2018). In regions where spring wheat is grown under irrigation, such as India, higher mean growingseason temperature is associated with lower yield (Asseng et al 2017).…”
Section: Introductionmentioning
confidence: 98%
“…Case studies on wheat yield trends and temperature variations have been reported from various countries (You et al 2009;Brisson et al 2010;Licker et al 2013;Tack et al 2015;Asseng et al 2017;Morgounov et al 2018). Yield loss of winter wheat in Kansas (USA) in 1985-2013 largely resulted from freezing temperatures in fall and extreme heat in spring during the growing season from September to May (Tack et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The connection between climate change, growing season length and agricultural production has been discussed by a number of researchers, for example, Børgesen and Olesen ( 2011 ); Ruosteenoja et al ( 2011 ), Øygarden et al ( 2014 ) for Northern European Countries and He et al ( 2018 ), Morgounov et al ( 2018 ) for North America. Most of these studies applied a model-based approach and did not use monitoring data that enables a retro-perspective view on this topic.…”
Section: Introductionmentioning
confidence: 99%